New Antibiotics for Lower Respiratory Tract Infections - Despoina Papageorgiou; Maria Gavatha; Dimitrios Efthymiou; Eleni Polyzou; Aristotelis Tsiakalos; Karolina Akinosoglou (Microbiology Research)
Respiratory tract infections are frequently encountered in clinical practice. The growing incidence of antimicrobial resistance among the causative pathogens exerts sustained pressure on the existing therapeutic options. The emergence of antimicrobial resistance limits the treatment options and often leads to unfavorable patient outcomes. However, in the past few years, newly developed antibiotics have become available, providing viable choices for antibiotic-resistant infections. New β-lactam/β-lactamase combinations, such as ceftazidime/avibactam, meropenem/vaborbactam, and imipenem/relebactam, are effective against carbapenem-resistant Enterobacterales. Several new drugs including ceftolozane/tazobactam are active against multi-drug-resistant Pseudomonas aeruginosa, while sulbactam/durlobactam and cefiderocol have potent activity against Acinetobacter baumannii. A number of new options, such as lefamulin, omadacycline, and delafloxacin, have also emerged for pathogens commonly associated with community acquired pneumonia. This article aims to review the characteristics of newly approved antibiotics for the treatment of respiratory tract infections, as well as to discuss some investigational agents that are currently under development.